Cholesterol Profile in The Dyslipidemia Patient Related to Pill Taking Time at Primary Healthcare in Purwokerto - Ika Mustikaningtias; Hening Pratiwi; Laksmi Maharani (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2020)
Dyslipidemia is a lipid metabolism disorder in Indonesians aged >15 years old. Pharmacokinetics and pharmacodynamics of Statin, the drug of choice for dyslipidemia, are influenced by circadian rhytms and thus require timing of pill taking time. The aims of this study are to determine relationship between the respondent characteristics to blood ccholesterol level and the effect of taking Simvastatin in the afternoon on the cholesterol level’s profile. The results showed that only body mass index (BMI) had an effect on cholesterol level (p=0,016) with Pearson correlation -0,685 (p=0,029). The cholesterol level is lower in respondents whose BMI is not ideal. The difference of pill taking time, at 18.00-21.00 and 21.00-24.00, did not show a difference profile of cholesterol level during one month of therapy. This results indicate that Simvastatin can be taken in the time range 18.00-24.00 to control cholesterol level of dyslipidemia patients.